Music processing deficits in Landau-Kleffner syndrome: Four case studies in adulthood. (August 2020) - Lévêque, Yohana; Roulet-Perez, Eliane; Deonna, Thierry; Moulin, Annie; Fornoni, Lesly; Mayor-Dubois, Claire; Caclin, Anne; Tillmann, Barbara
Abstract: Verbal-auditory agnosia and aphasia are the most prominent symptoms in Landau-Kleffner syndrome (LKS), a childhood epilepsy that can have sustained long-term effects on language processing. The present study provides the first objective investigation of music perception skills in four adult patients with a diagnosis of LKS during childhood, covering the spectrum of severity of the syndrome from mild to severe. Pitch discrimination, short-term memory for melodic, rhythmic and verbal information, as well as emotion recognition in music and speech prosody were assessed with listening tests, and subjective attitude to music with a questionnaire. We observed amusia in 3 out of 4 patients, with elevated pitch discrimination thresholds and poor short-term memory for melody and rhythm. The two patients with the most severe LKS had impairments in music and prosody emotion recognition, but normal perception of emotional intensity of music. Overall, performance in music processing tasks was proportional to the severity of the syndrome. Nonetheless, the four patients reported that they enjoyed music, felt musical emotions, and used music in their daily life. These new data support the hypothesis that, beyond verbal impairments, cerebral networks involved in sound processing and encoding are deeply altered by the epileptic activity in LKS, well after electrophysiological normalization.